Elements of Commerce Shows Enterprise Development Innovation Efficient Auditing and the Way of the Future - Gunawan Pamudji Widodo; Muhammad Syukri (ADI Publisher, 2021)
Technological entrepreneurship helps create sustainable value, accelerate corporate growth and promote economic sustainability through the capitalization and commercialization of innovative new technologies. There are obstacles in conducting Business Model Innovation (BMI) as a reference form of technological entrepreneurship as a reference. This study aims to establish a business model for developing the economy with technological entrepreneurship innovation (BMIfTE). Readiness is one of the keys in carrying out a goal, because there are things that must be prepared, such as the topics discussed in papers related to previous researchers who have published the development of a BMIfTE. For this reason, the paper in this study discusses opportunities and risks, value transitions, economic development, strategies for companies, dynamic capabilities and stakeholders. The new proposal is a form of BMI reconstruction regarding the business model in function of technology to create new systems and methods to take advantage of existing business development opportunities to be able to compete and stand in the national market.